Carceral circuitry: New directions in carceral geography. (April 2018) - Gill, Nick; Conlon, Deirdre; Moran, Dominique; Burridge, Andrew
Despite the popular impression of prisons and other carceral spaces as disconnected from broader social systems, they are traversed by various circulations that reach within and beyond their boundaries. This article opens a new analytical window onto this reality, developing the concept of 'circuits' to critically enquire into the carceral. Drawing inspiration from Harvey (1982; 1985), the article makes circuits do fresh work, teasing apart the emerging carceral landscape to provide a new critical epistemology for carceral geographies. In so doing, a meta-institutional agenda for critical carceral geography is derived, and possible ways to short-circuit carceral systems are revealed.